2007
DOI: 10.1037/0894-4105.21.4.401
|View full text |Cite
|
Sign up to set email alerts
|

Implications of within-person variability in cognitive and neuropsychological functioning for the interpretation of change.

Abstract: Samples of adults across a wide age range performed a battery of 16 cognitive tests in 3 sessions within an interval of approximately 2 weeks. Estimates of within-person variability across the 3 assessments were relatively large and were equivalent in magnitude to the cross-sectional age differences expected over an interval of 15-25 years. These findings raise questions about the precision of assessments based on a single measurement and imply that it may be difficult to distinguish true change from short-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 21 publications
4
98
0
Order By: Relevance
“…The dataset was aggregated from seven different studies conducted since 2001 at the Cognitive Aging Lab at the University of Virginia (Salthouse, 2007;Salthouse, Atkinson, & Berish, 2003;Salthouse, Berish, & Siedlecki, 2004;Salthouse & Ferrer-Caja, 2003;Salthouse, Nesselroade, & Berish, 2006;Salthouse, Pink, & Tucker-Drob, in press;Salthouse & Siedlecki, 2007;Salthouse, Siedlecki, & Krueger, 2006). Participants were recruited with newspaper advertisements, flyers, and referrals from other participants.…”
Section: Methods Participantsmentioning
confidence: 99%
“…The dataset was aggregated from seven different studies conducted since 2001 at the Cognitive Aging Lab at the University of Virginia (Salthouse, 2007;Salthouse, Atkinson, & Berish, 2003;Salthouse, Berish, & Siedlecki, 2004;Salthouse & Ferrer-Caja, 2003;Salthouse, Nesselroade, & Berish, 2006;Salthouse, Pink, & Tucker-Drob, in press;Salthouse & Siedlecki, 2007;Salthouse, Siedlecki, & Krueger, 2006). Participants were recruited with newspaper advertisements, flyers, and referrals from other participants.…”
Section: Methods Participantsmentioning
confidence: 99%
“…There is still some controversy with respect to age differences in older adults. Note, however, that those studies that have reported a lack of age differences in IIV either have relied on accuracy scores rather than RTs in experimental tasks (e.g., Robertson, Myerson, & Hale, 2006) or have studied variability in a task repeated within a short period of time; in the latter case, IIV was computed on relatively few occasions and/or on the number of correct responses within a limited time rather than on RTs (e.g., Salthouse, 2007;Salthouse & Berish, 2005;Salthouse & Nesselroade, 2010).…”
Section: Intraindividual Variabilitymentioning
confidence: 99%
“…Some of these effects can be illustrated with a comparison of reliabilities of measures across different types of aggregation. Because participants in VCAP performed different versions of the same tests on three sessions each separated by approximately 1 week (e.g., Salthouse, 2007), reliability can be assessed with the correlation of relevant scores across the first and second sessions. The across-session correlations were .75 for a measure of word recall based on the sum of items recalled across 4 repetitions of the same 12-word list; .85 for a composite memory measure based on the average z-score for word recall, paired associates, and logical memory measures; and .96 for a latent variable based on the same 3 memory measures.…”
Section: Improving Measurementmentioning
confidence: 99%